Mesoporous Silica Hybridized With Gadolinium(III) Nanoplatform for Targeted Magnetic Imaging-Guided Photothermal Breast Cancer Therapy - Longqing Wang; Xiaofeng Sun (SAGE Publishing, 2020)
Achieving drug target accumulation in antitumor tissue, simultaneous diagnostic imaging, and optimal release behavior with treatment needs a best chemotherapy procedure involving receptive switch of drug delivery. Constructed on mesoporous silica nanoparticles, which are crossed with multiscale charming nanoparticles for magnetic resonance imaging (MRI)-aided and alternate magnetic field (AMF) response chemotherapy for breast cancer, we report in this work the assembly of a new theranostics drug conveyance process. Hydrothermal processes (gadolinium(III) oxide nanoparticles [Gd-NPs]) and heat decomposition process (radical size uFe-NPs) were used to prepare superparamagnetic Gd-NPs with multiscale sizes. Gadolinium(III) oxide nanoparticles act as an AMF-responsive heat mediator, while ultra-Fe nanoparticles (uFe-NPs) act as an MRI T 2 contrast mediator. Nanoparticles of the mesoporous silica with radially oriented mesochannels were further grown in situ on the surfaces of the Gd-NPs, and the uFe-NPs anticancer drug doxorubicin can be easily incorporated in the mesochannels. To provide better targeting capabilities for the as-synthesized biotin-loaded nanohybrids, the particle surfaces are updated with biotin (Bt). This optimized drug conveyance method based on nanocomposites of SiO 2 demonstrated great efficiency of medication charging and receptive properties of AMF stimulus release. However, tests of MRI in vitro showed an outstanding contrast effect in MRI with a high stimulation quality (299 mM −1 s −1 ). In contrast, the study of in vitro cytotoxicity assessment revealed that an MRI-directed stimulus-mediated theranostics tool can be used as a drug conveyance device to efficiently treat breast cancer.